Andrographolide Inhibits ER-Positive Breast Cancer Growth and Enhances Fulvestrant Efficacy via ROS-FOXM1-ER-α Axis - Xu, Tong; Jiang, Yanyu; Yuan, Shuying; Zhang, Li; Chen, Xihui; Zhao, Weili; Cai, Lili; Xiao, Biying; Jia, Lijun (Frontiers in Oncology, 2022)
Estrogen receptor (ER)-positive breast cancer is the main subtype of breast cancer (BRCA) with high incidence and mortality. Andrographolide (AD), a major active component derived from the traditional Chinese medicine Andrographis paniculate, has substantial anti-cancer effect in various tumors. However, the antitumor efficacy and the underlying molecular mechanisms of AD on ER-positive breast cancer are poorly understood. In the present study, we demonstrated that andrographolide (AD) significantly inhibited the growth of ER-positive breast cancer cells. Mechanistically, AD suppressed estrogen receptor 1 (ESR1, encodes ER-α) transcription to inhibit tumor growth. Further studies revealed that AD induced ROS production to down-regulate FOXM1-ER-α axis. Conversely, inhibiting ROS production with N-acetylcysteine (NAC) elevated AD-decreased ER-α expression, which could be alleviated by FOXM1 knockdown. In addition, AD in combination with fulvestrant (FUL) synergistically down-regulated ER-α expression to inhibit ER-positive breast cancer both in vitro and in vivo. These findings collectively indicate that AD suppresses ESR1 transcription through ROS-FOXM1 axis to inhibit ER-positive breast cancer growth and suggest that AD might be a potential therapeutic agent and fulvestrant sensitizer for ER-positive breast cancer treatment.